Partisans of Allah : Jihad in South Asia - Jalal, Ayesha (Cambridge, Mass. : Harvard University Press, 2008)
Today, more than ever, jihad signifies the political opposition between Islam and the West. As the line drawn between Muslims and non-Muslims becomes more rigid, Jalal seeks to retrieve the ethical meanings of this core Islamic principle in South Asian history. Drawing on historical, legal, and literary sources, Jalal traces the intellectual itinerary of jihad through several centuries and across the territory connecting the Middle East with South Asia.
Jihad as ethics, Jihad as war -- Jihad in precolonial South Asia -- The martyrs of Balakot -- Jihad in colonial India -- Jihad as anticolonial nationalism -- Islam subverted? Jihad as terrorism -- Conclusion.
Includes bibliographical references (pages 321-355) and index.
Print version record.
In English.
Master record variable field(s) change: 650
Keywords: Jihad; Martyrdom -- Islam; Muslim martyrs -- South Asia; Islam and politics -- South Asia; RELIGION -- Islam -- General; RELIGION -- Islam -- History; Islam and politics; Jihad; Martyrdom -- Islam; Muslim martyrs; South Asia; Andere Religionen; Asia-Pacific.; Culture and History of non-European Territories; History; Islam and politics; Jihad; Muslim martyrs; Electronic books